2023
DOI: 10.1038/s41422-023-00779-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of activation and biased signaling in complement receptor C5aR1

Abstract: The complement system plays an important role in the innate immune response to invading pathogens. The complement fragment C5a is one of its important effector components and exerts diverse physiological functions through activation of the C5a receptor 1 (C5aR1) and associated downstream G protein and β-arrestin signaling pathways. Dysfunction of the C5a-C5aR1 axis is linked to numerous inflammatory and immune-mediated diseases, but the structural basis for activation and biased signaling of C5aR1 remains elus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…It is evident from the binary and ternary complex (Figure 1) structures that the Helix2‐L 2 ‐Helix3‐L 3 region and the CT‐peptide region (I65–R74) of C5a are collectively involved in binding to the receptors. The cryo‐EM ternary complex data indicates that R74 of C5a interacts with D282 of C5aR1 6,7 . Moreover, C5a fails to trigger the activation of G‐protein through D282A and D282E mutants of C5aR1.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…It is evident from the binary and ternary complex (Figure 1) structures that the Helix2‐L 2 ‐Helix3‐L 3 region and the CT‐peptide region (I65–R74) of C5a are collectively involved in binding to the receptors. The cryo‐EM ternary complex data indicates that R74 of C5a interacts with D282 of C5aR1 6,7 . Moreover, C5a fails to trigger the activation of G‐protein through D282A and D282E mutants of C5aR1.…”
Section: Discussionmentioning
confidence: 96%
“…The cryo-EM ternary complex data indicates that R74 of C5a interacts with D282 of C5aR1. 6,7 Moreover, C5a fails to trigger the activation of G-protein through D282A and D282E mutants of C5aR1. Further, it is observed that R74 can form a "cation-π" interaction with Y258 of C5aR1.…”
Section: Estimating the Binding Free Energy Of The Antibody-like Pept...mentioning
confidence: 99%
See 3 more Smart Citations